Performance of random diagonal code for OCDMA systems using new spectral direct detection technique - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid; R. Badlishah, Ahmad (Elsevier Inc, 2009)
Link to publisher's homepage at http://www.elsevier.com